Leader–Member Exchange (LMX) and Performance: A Meta‐Analytic Review. Issue 1 (25th April 2015) - Martin, Robin; Guillaume, Yves; Thomas, Geoff; Lee, Allan; Epitropaki, Olga
Abstract : This paper reports a meta‐analysis that examines the relationship between leader–member exchange (LMX) relationship quality and a multidimensional model of work performance (task, citizenship, and counterproductive performance). The results show a positive relationship between LMX and task performance (146 samples, ρ = .30) as well as citizenship performance (97 samples, ρ = .34), and negatively with counterproductive performance (19 samples, ρ = ‒.24). Of note, there was a positive relationship between LMX and objective task performance (20 samples, ρ = .24). Trust, motivation, empowerment, and job satisfaction mediated the relationship between LMX and task and citizenship performance with trust in the leader having the largest effect. There was no difference due to LMX measurement instrument (e.g., LMX7, LMX‐MDM). Overall, the relationship between LMX and performance was weaker when (a) measures were obtained from a different source or method and (b) LMX was measured by the follower than the leader (with common source‐ and method‐biased effects stronger for leader‐rated LMX quality). Finally, there was evidence for LMX leading to task performance but not for reverse or reciprocal directions of effects.